P/Q‐ and N‐type calcium‐channel antibodies: Oncological, neurological, and serological accompaniments. Issue 2 (8th February 2016) - Zalewski, Nicholas L.; Lennon, Vanda A.; Lachance, Daniel H.; Klein, Christopher J.; Pittock, Sean J.; Mckeon, Andrew
ABSTRACT: Introduction: Voltage‐gated calcium‐channel autoimmunity (VGCC‐P/Q and VGCC‐N types) occurs beyond Lambert–Eaton syndrome and lung cancer. Methods: We reviewed records for 236 Mayo Clinic patients with VGCC antibodies found in evaluation for paraneoplastic neurological autoimmunity (generally without myasthenic syndromes). Results: VGCC autoantibodies were detected in 3.4% of neurological patients, 1.7% of healthy controls, and 4% of neurologically asymptomatic lung cancer controls. Fifty neurological patients (21%) had ≥ 1 neoplasm, historically (46) or detected prospectively [small‐cell lung carcinoma (2), breast adenocarcinoma (2), lymphoma (1), and suspected tonsillar carcinoma (1)]. Autoimmune neurological diagnosis frequencies (encephalopathy, ataxia, myelopathy, neuropathy, neuromuscular junction disorder, and myopathy) among patients with medium values (24%; 0.10–0.99 nmol/L) or low values (19%; 0.03–0.10 nmol/L) were fewer than among patients with antibody values exceeding 1.00 nmol/L (71%; P = 0.02 and 0.004, respectively). Conclusions: Among neuronal VGCC‐autoantibody–seropositive patients, autoimmune neurological phenotypes and cancer types are diverse. Cautious interpretation of results (particularly medium and low values) is advised. Muscle Nerve, 2016 Muscle Nerve 54 : 220–227, 2016